Strategic leadership and innovation at Apple Inc. - Heracleous, Loizos Th., (SAGE Knowledge. Cases., 2016)
The case describes the successful tenure of Steve Jobs as CEO of Apple and how he succeeded in creating one of the wealthiest and most innovative companies in the world. The student is invited to consider what will happen to the company after Steve Jobs' death under the leadership of Tim Cook and whether Apple can replicate its success of previous years.